Spinal fusion techniques - Abd-Elsayed, Alaa (Atlas of interventional pain management series., 2024)
"Spinal Fusion Techniques, a volume in the Atlas of Interventional Pain Management series, is a concise, practical guide that provides clinicians with detailed, step-by-step guidance on how to perform the latest interventional techniques for treating patients with chronic pain as a result of spinal stenosis. This comprehensive, easy-to-follow guide offers expert coverage of how to deliver safe, accurate, and cost-effective pain relief to patients using all clinically useful imaging modalities, including ultrasound-guided techniques and fluoroscopy. With high-quality images and clear, authoritative guidance throughout, it shows exactly how to evaluate the causes of pain, identify the most promising stimulation technique, locate the site with precision, and deliver effective relief"--